Komunikasi Data Antara Modul MMI (Man Machine Interface) dan Modul Scrambler/Descrambler pada Telepon Scrambler - Herlan Herlan; Ade Ramdan (Pusat Penelitian Informatika - LIPI, 2012)
This paper proposes a data communication system between MMI module with scrambler/descrambler module. The system is designed and implemented on a scrambler phone. The trasmitted data is needed to determine the speed of randomization sound signal processes and patterns. The data is transmitted through microcontroller based serial communication. A data communication protocol is designed to perform data communication between two modules. The experiment shows serial data communication between the MMI module and the scrambler/ descrambler module with 1200 bps data transmission speed is working properly without errors by a proof that the scrambler/descrambler module sends a